Nano-magnetite decorated carbon fibre for enhanced interfacial shear strength. (July 2019) - Fakhrhoseini, Seyed Mousa; Li, Quanxiang; Unnikrishnan, Vishnu; Naebe, Minoo
Abstract: The modification of carbon fibres surface has been achieved by high temperature (1000 °C) growth of Fe3 O4 magnetic nanoparticles (MNPs) on the surface of carbon fibres using ammonium iron (II) sulphate as a single precursor of the nanoparticles. As a consequence, the formation of MNPs on the surface of unsized carbon fibres increased the interfacial shear strength by 84.3%, as measured by single fibre fragmentation test. Further investigation on interfacial reinforcing mechanism confirmed an increase in average total surface energy of carbon fibres from 58.81 for unmodified carbon fibre to 64.31 mJ/m 2 for MNPs decorated fibres. Fundamental analysis revealed a 12.44% increase in average dispersive and no significant reduction in average specific surface energy of carbon fibre after MNPs surface decoration. This led to an increase in interlaminar shear strength from 46.9 to 63.3 MPa due to the strong mechanical interlocking at the MNPs decorated-carbon fibre/epoxy interface which can be described by improve in the dispersive component of the surface energy. Graphical abstract: Image 1